Examination about more realistic prognosis evaluation method, how long the patients with congestive heart failure can spend at home. (14th October 2021) - Takaishi, A; Iida, T; Kishinoue, T; Mori, H; Yamaji, T; Tanimoto, M; Onishi, N; Hirohata, S; Ueeda, M; Ito, H
Abstract: Background: From August 2015, for efficient medical care in congestive heart failure (CHF) cases, we had introduced a unique clinical pathway (PATH) provided the immediate use of Tolvaptan and comprehensive education by multi-disciplinary staff after admission. And by introduction of PATH, we confirmed the shortening effect of hospitalization period with CHF and the suppressive effect of readmission with CHF after discharge. But since almost CHF patients repeat hospitalization and discharge due to change of their medical condition, the investigation for only first readmission rate after discharge is not enough to assess the entire long clinical course of CHF. Recently we found one report about evaluation method for CHF clinical prognosis, how long CHF patients can stay healthy at their own home after discharge within a certain period. This evaluation method is considered to take into account the long clinical course of CHF. Purpose: We investigated whether the CHF patients introduced PATH on admission could stay longer at their home than CHF patients without PATH. Methods: Between April 2014 and July 2019, 471 CHF cases, who ware admitted in our hospital at first and could be followed up for at least 1 month after discharge, ware enrolled. We divided them to two groups, PATH- group before introducing PATH (until July 2015, 142 cases), and PATH+ group applied PATH (after August 2015, 329 cases). Between both groups, we investigated the readmission rate (RR) with CHF and the total period (TP) that patients could spend at home within1, 3, 6 and 12month after discharge. Results: There were no significant differences in mean age, pre-hospital living status, or clinical status at admission between the two groups. On the other hand, due to efficient CHF care, the average length of hospital stay was significantly shorter (figure1). RR within 1, 3, 6 and 12 months after discharge ware all lower in PATH+ group. And TP within 1, 3, 6 and 12 months after discharge ware all longer in PATH+ group (figure2). Conclusion: By introducing our unique clinical pathway for congestive heart failure cases requiring hospitalization, we could confirm not only the improvement of their conventional clinical prognosis index but also the improvement of their new and more realistic clinical prognosis index after discharge. Funding Acknowledgement: Type of funding sources: None.